2011
DOI: 10.1128/cvi.00472-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antibody Responses to Mycobacterium leprae Phenolic Glycolipid I, Lipoarabinomannan, and Recombinant Proteins To Define Disease Subtype-Specific Antigenic Profiles in Leprosy

Abstract: A simple serodiagnostic test based on the Mycobacterium leprae-specific phenolic glycolipid I(PGL-I), for individuals with leprosy is nearly universally positive in leprosy patients with high bacillary loads but cannot be used as a stand-alone diagnostic test for the entire spectrum of the disease process. For patients with early infection with no detectable acid-fast bacilli in lesions or with low or no antibody titer to PGL-I, as in those at the tuberculoid end of the disease spectrum, this diagnostic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 31 publications
1
42
0
3
Order By: Relevance
“…To date, leprosy rapid diagnostic tests have comprised only PGL-I mimetics as the antigenic target (ML Flow test and Standard Diagnostics leprosy test [hereinafter called SD Leprosy], containing tri-or disaccharides NTP and NDO, respectively) (14-17). Using laboratory-based assays, our group and others have identified numerous native and recombinant proteins recognized by antibodies in MB leprosy patient serum (18)(19)(20)(21)(22)(23)(24)(25). One example is the chimeric fusion protein leprosy IDRI diagnostic 1 (LID-1), an antigen specifically recognized by sera from leprosy patients from geographically and ethnically diverse populations, with a direct correlation between seroreactivity and BI (18,(26)(27)(28).…”
mentioning
confidence: 99%
“…To date, leprosy rapid diagnostic tests have comprised only PGL-I mimetics as the antigenic target (ML Flow test and Standard Diagnostics leprosy test [hereinafter called SD Leprosy], containing tri-or disaccharides NTP and NDO, respectively) (14-17). Using laboratory-based assays, our group and others have identified numerous native and recombinant proteins recognized by antibodies in MB leprosy patient serum (18)(19)(20)(21)(22)(23)(24)(25). One example is the chimeric fusion protein leprosy IDRI diagnostic 1 (LID-1), an antigen specifically recognized by sera from leprosy patients from geographically and ethnically diverse populations, with a direct correlation between seroreactivity and BI (18,(26)(27)(28).…”
mentioning
confidence: 99%
“…These results suggest that M. bovis Ag85B contains one or several epitopes specifically recognized by sera of LL patients (9). A recent report demonstrated that M. leprae recombinant Ag85B (ML2028) is an ideal candidate for use for leprosy serodiagnosis, as it is recognized by sera from all leprosy patients, regardless of their clinical classification (35).…”
Section: Discussionmentioning
confidence: 98%
“…It was not determined whether the LL patients developed leprosy type 1 or type 2 reactions. Sera from cavitary TB patients were provided by William MacKenzie through a serum bank repository from the Centers for Disease Control, Atlanta, GA (23). All TB patients were smear positive.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were coded to protect donor identities and collected with informed consent and with permission from the institutional review boards of the relevant countries and institutions involved, as described by Spencer et al (23). All leprosy patient sera were obtained from newly diagnosed individuals prior to their receiving the multidrug regimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation